TRANSLATION AS A KEY AND A MIRROR: RECEPTION OF SERBIAN LITERATURE IN TODAY’S UKRAINE - Tatarenko, Alla (Porównania, 2019)
The objective of this paper is to identify the main trends in the representation of Serbian literature in Ukraine during the last twenty years, to trace the ways and means of shaping the corpus of the Serbian literature translated into Ukrainian, to determine the factors influencing the reception of Serbian belles-lettres in Ukraine, as well as changes taking place in translation policies, publishing strategies and formats of presenting translations. Translation is considered the key to understanding and identifying another nation as well as a mirror in which the reader not only sees the reflection of the Other, but also investigates their own face.